Concussion knowledge and experience among Welsh amateur rugby union coaches and referees. Issue 1 (11th September 2017) - Griffin, Steffan Arthur; Ranson, Craig; Moore, Isabel; Mathema, Prabhat
Abstract : Background: Rugby union is a collision sport where participants are at high risk of sustaining a concussion. In settings where there is little qualified medical supervision, certain stakeholders (eg, coaches and officials) should possess sufficient knowledge in regard to the recognition and management of concussion. Aim: The aim of this study was to assess the knowledge and experience of various aspects of concussion among coaches and referees involved in Welsh amateur rugby union. Methods: A questionnaire was distributed to 1843 coaches and 420 referees. Results: A total of 333 coaches and 283 referees completed the questionnaire (18% and 68% response rates, respectively). Participants exhibited greater knowledge of concussion symptom recognition relative to knowledge of both the consequences of concussion and associated return-to-play protocols, both of which could be considered poor. There were no differences in knowledge levels between coaches and referees or between participants with or without a history of concussion. Two-thirds of participants incorrectly believed that headgear could prevent concussion, and nearly 30% of coaches reported having witnessed other coaches allowing a potentially concussed player to continue playing. Conclusions: Identification of several misconceptions indicates that concussion management within Welsh amateur rugby union needs to be improved, warranting a multi-faceted educational intervention.